Comparative study of pseudo-static finite element analysis and closed-form solutions of circular tunnels embedded in soft soil and rock - Nursyafikah Hafizi; Siti Khadijah Che Osmi; Faizzuan Fazully; Maidiana Othman (Penerbit Universiti Kebangsaan Malaysia, 2024)
The occurrence of earthquake events has caused numerous causalities and economic losses within the construction industry in the past and present years. However, people have insufficient knowledge and awareness of the impact of earthquakes, especially in understanding the seismic response of complex underground construction industries such as tunneling. Careful consideration of the impact of earthquakes on such structures is crucial due to previous experiences of catastrophic earthquake events that severely damaged underground structures. This study aims to investigate the effect of different soil material properties (i.e., soft soil and rock) on the seismic response of circular tunnels under increasing earthquake ground motion using simplified pseudo-static analysis, while simultaneously emphasizing the shortcomings of conventional closed-form solutions. To achieve this, a two-dimensional (2D) simplified pseudo-static analysis of a soil-tunnel model embedded at 20m depth was investigated under increasing levels of seismic intensity at the transverse direction of the tunnel axis using PLAXIS 2D software. The tunnel is modeled as a circular shape with a 0.5m thick tunnel lining embedded at a depth of 20 m from the ground surface in two different types of soil profiles i.e. soft soil and rock. The soil is treated as a single-phase medium without excess pore pressure. The six seismic intensities of peak ground acceleration (PGA) ranging from 0.1g to 0.6g were considered in this study. For validation purposes, the numerical results of pseudo-static analyses were verified with the analytical closed-form solution using Wang’s method 1993. The findings indicate that the tunnel embedded in soft soil experienced maximum structural forces for bending moments and axial forces compared to rock. Results denoted that the seismic responses of the tunnel increased with the increment of earthquake magnitude and its epicenter. Notably, the results of analytical methods seemed to be underestimated compared to numerical analyses.